Some evidence of poverty redution through improved agricultural performance in the developing world - Ahmad Anwar Mohamed Ismail (2011)
History shows that different rates of poverty reduction over the past five decades have been closely related to differences in agricultural performance - particularly the rate of growth of agricultural productivity.In Asia, the rapid productivity gains of the Green Revolution increased producers, income, raised labourers, wages and lowered the price of food. In addition, new livelihood opportunities were generated when success in agriculture provided the basis for economic diversification. However, despite decades of investment in new agricultural technology and rural development, hunger and poverty continue to plague large areas of the developing world. The problem is particularly acute in sub-Saharam Africa, where progress towards the Millennium Development Goals is slowest.While increasing agricultural productivity perhaps remains the single most important determinant of economic growth and poverty reduction, serious doubts are emerging as to whether agricultural productivity can be futher increased, where it is most needed and what part, if any, small scale farming will play in future. Development experts need greater understanding of the links between agricultural productivity and poverty. They also need to asess just how far they have changed and the extent to which small scale agriculture can remain a ladder out of poverty for millions of people living in rural areas.In this paper what we know of the impact of agricultural performance on poverty reduction in the developing world is reviewed, while some emerging issues and questions that arose are addressed. This paper is intended solely to stimulate public discussion.